MANAJEMEN STRATEGIS iMADIUN DALAM MENINGKATKAN MINAT BACA MASYARAKAT KOTA MADIUN DI PERPUSTAKAAN KOTA MADIUN - Alif Widya Nurrochma; Meirinawati Meirinawati (Universitas Negeri Surabaya, 2022)
The application of digital libraries is one way to increase the reading interest of people who are now more familiar with digitalization. Offering faster and easier access, digital libraries have been chosen to be one way to increase interest in reading. iMadiun is one of the digital libraries in Madiun Residency. As one of the pioneers of the first digital library in the Madiun Residency, iMadiun still has several problems, such as the length of verification of the registration email by the admin, the application is only available for the android version, so there are still errors application. This problem needs to be fixed so that the iMadiun application service can help increase people's reading interest. This research was conducted with the aim of knowing and analyzing the right strategy in increasing public interest in reading through iMadiun based on a SWOT analysis. The research method used in this research is descriptive qualitative with SWOT analysis data analysis technique (Strength, Weakness, Opportunity, Threat). SWOT analysis was carried out using primary and secondary data obtained by data collection techniques through in-depth interviews, observation and study of related documents. Then by using indicators and taking the right strategy from the SWOT analysis, it is hoped that it can provide a better plan for maximizing the potential of iMadiun in increasing public interest in reading. Keywords: strategic management, iMadiun, SWOT analysis